1999
DOI: 10.1093/jac/43.suppl_3.37
|View full text |Cite
|
Sign up to set email alerts
|

Comparative in-vitro activity of levofloxacin against isolates of bacteria from adult patients with community-acquired lower respiratory tract infections

Abstract: This study was conducted to evaluate the activity of levofloxacin in comparison with a range of antibacterial agents against recent isolates obtained consecutively from patients with community-acquired pneumonia (CAP) or acute exacerbation of chronic bronchitis (AECB) during the period 1995 to 1996. Susceptibility testing was carried out by either microdilution or the Etest, and interpreted according to NCCLS breakpoints. The activity of levofloxacin was compared with that of amoxycillin, amoxycillin-clavulana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
1

Year Published

2000
2000
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 21 publications
1
3
1
Order By: Relevance
“…In contrast to others [16,18,21,22], we did notice a reduced susceptibility to levofloxacin and ciprofloxacin of P. aeruginosa, still an important and frequent pathogen in neutropenic patients. Further, a partial (70%) cross-resistance occurred in P. aeruginosa isolates, thus confirming the recent finding by Segatore et al [21] who assessed the activity of levofloxacin against P. aeruginosa isolated from intensive care units, and haematology and oncology wards.…”
Section: Discussioncontrasting
confidence: 99%
“…In contrast to others [16,18,21,22], we did notice a reduced susceptibility to levofloxacin and ciprofloxacin of P. aeruginosa, still an important and frequent pathogen in neutropenic patients. Further, a partial (70%) cross-resistance occurred in P. aeruginosa isolates, thus confirming the recent finding by Segatore et al [21] who assessed the activity of levofloxacin against P. aeruginosa isolated from intensive care units, and haematology and oncology wards.…”
Section: Discussioncontrasting
confidence: 99%
“…The American Thoracic Society guidelines stress the use of empirical treatment as pathogen identification can be difficult [1]. We found that ampicillin, co-amoxiclav, fluoroquinolone, secondgeneration cephalosporin, erythromycin and tetracycline can be used empirically in the treatment of CAP, while aminoglycosides and imipenem can be used in HAP, a finding in agreement with the recommendations of others [1,2,15,[22][23][24][25][26][27][28]. Mortality from pneumonia (both CAP and HAP) has been reported to range from 10 to 70% [13,[29][30][31], with a better prognosis for CAP than HAP [32], a finding similar to our own.…”
Section: Discussionsupporting
confidence: 88%
“…Mycoplasma, Legionella sp., Chlamydia pneumoniae) can account for 30% of the cases of CAP [2,10]. Other pathogens include H. influenzae, Staphylococcus aureus, and M. catarrhalis [11][12][13][14][15]. Our study showed that S. pneumoniae was isolated in only 3% of the cases of CAP while H. influenzae was the commonest Number and percent (in parentheses) are given.…”
Section: Discussionmentioning
confidence: 79%
“…Levofloxacin provides a useful empiric alternative to ciprofloxacin for patients in whom the role of P aeruginosa is unclear and for whom broader coverage for atypical and Grampositive pathogens also is desired. 33 Newer fluoroquinolones lose activity against Pseudomonas but increase activity against atypical, Gram-positive, and anaerobic pathogens. Unfortunately, the treatment of acute purulent exacerbations of chronic bronchitis with a fluoroquinolone can induce resistant isolates.…”
Section: Fluoroquinolones For Respiratory Infectionsmentioning
confidence: 99%